1990
DOI: 10.1037/0022-3514.59.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation and contrast as a function of people's willingness and ability to expend effort in forming an impression.

Abstract: Set/reset (Martin, 1986) hypothesis that contrast demands more cognitive effort than does assimilation was examined. In Exp. 1, the impressions of distracted Ss showed assimilation toward blatantly primed concepts, whereas the impressions of nondistracted Ss showed contrast. In Exp. 2, Ss told that their ratings would be lumped into a group average showed assimilation, whereas Ss told that their ratings would be examined individually showed contrast. In Exp. 3, the impressions of Ss low in need for cognition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
360
2
9

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(392 citation statements)
references
References 42 publications
21
360
2
9
Order By: Relevance
“…Although this particular finding was not originally expected, it is not entirely inconsistent with our conceptualization. Previous studies have shown that when people consciously attempt to exclude from their judgments contextual inputs (e.g., incidental feelings) that are readily accessible, they sometimes over-correct, resulting in a contrast effect in the final judgment (Martin, Seta, and Crelia 1990;Ottati and Isbell 1996;Schwarz and Bless 1992). It is therefore possible that when participants with an experiential motive attempted to disregard their otherwise relevant feelings in the distant-future condition, they over-corrected for the influence of their mood state, resulting in mood-incongruent intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Although this particular finding was not originally expected, it is not entirely inconsistent with our conceptualization. Previous studies have shown that when people consciously attempt to exclude from their judgments contextual inputs (e.g., incidental feelings) that are readily accessible, they sometimes over-correct, resulting in a contrast effect in the final judgment (Martin, Seta, and Crelia 1990;Ottati and Isbell 1996;Schwarz and Bless 1992). It is therefore possible that when participants with an experiential motive attempted to disregard their otherwise relevant feelings in the distant-future condition, they over-corrected for the influence of their mood state, resulting in mood-incongruent intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Schwarz and Bless (1992) have argued that there are processes guiding contrast effects other than changes in standards. For example, Martin and his colleagues (Martin, 1986;Martin, Seta, & Crelia, 1990) have explored the cognitive processes involved in one type of contrastive process, which they refer to as a reset or category inhibition process. The reset process appears to demand more cognitive resources than associative-based assimilation processes.…”
Section: Using Range-frequency Theory To Understand Social Judgmentsmentioning
confidence: 99%
“…The memorization tasks manipulate available working memory. Extensive literature documents that cognitive resources are bounded and that increasing CL can affect judgments (Cornelissen, Dewitte, & Warlop, 2011;Hinson, Jameson, & Whitney, 2003;Swann, Hixon, SteinSeroussi, & Gilbert, 1990;Van den Bos, Peters, Bobocel, & Ybema, 2006), limit the ability to process information (Gilbert, Pelham, & Krull, 1988), decrease self-control (Mann & Ward, 2007;Shiv & Fedorikhin, 1999;Ward & Mann, 2000), affect strategic behavior (Allred, Duffy, & Smith, 2016;Duffy & Smith, 2014;Duffy, Owens & Smith, unpublished), increase the assimilation effect (Martin, Seta, & Crelia, 1990), affect duration judgments (Block, Hancock, & Zakay, 2010), and prompt stereotyping (Wigboldus, Sherman, Franzese, & van Knippenberg, 2004).…”
mentioning
confidence: 99%